Size‐dependent nutrient limitation of tree growth from subtropical to cold temperate forests. (18th September 2017) - Li, Yong; Tian, Dashuan; Yang, Hao; Niu, Shuli
Abstract: The traditional paradigm is that plant growth at high latitudes is generally nitrogen (N) limited, whereas phosphorus (P) limitation occurs at low latitudes. However, this latitudinal pattern of nutrient limitation is not empirically tested and the underlying mechanisms are far from clear. Here we performed a coordinated experiment of N and/or P addition at three forest sites in China, a subtropical forest, a warm‐temperate forest and a cold‐temperate forest. By measuring relative growth rate (RGR) and leaf nutrient traits among different tree size groups, we assessed how they vary with nutrient addition and tree sizes and uncovered the likely mechanisms underlying these observed responses. Our results revealed that P addition enhanced the RGR of small trees (DBH < 15 cm) by 41% in subtropical forest and 114% in warm‐temperate forest, but reduced it by 57% in cold‐temperate forest. Moreover, small tree RGR increased linearly with soil available P at subtropical and warm‐temperate sites, while it followed a quadratic relationship with soil available N:P ratio at a cold‐temperate site. N addition only affected small tree RGR at the cold‐temperate site. In contrast, the RGR of large trees (DBH > 15 cm) was not impacted by any nutrient addition treatment or soil nutrient variations at any site. Leaf P concentration and resorption efficiency in both small and large trees mostly showed a linear response to soil available P at subtropical and warm‐temperate sites, while leaf N:P ratio in small trees elevated linearly with soil available N:P ratio at a cold‐temperate site. Overall, this study presents robust experimental evidence that growth in small trees, not large trees, is primarily limited by P in subtropical and warm‐temperate forests, but is co‐limited by N and P in cold‐temperate forests. This size‐dependent nutrient limitation highlights the importance of considering tree size classes when assessing nutrient limitation in forest. A plain language summary is available for this article. Abstract : Plain Language Summary